Neoadjuvant Radiation with Concurrent 5-FU Resulting in Complete Pathologic Response in Stage IIIB Squamous Cell Carcinoma of the Urethra - Krishna H. Suthar; Meghana Kesireddy; Mark Sides; Amit Correa; Aijan Ukudeyva; Rohit Venkatesan (Case Reports in Oncological Medicine)
Squamous cell carcinoma (SCC) of the urethra is a rare malignancy, comprising less than 1% of all malignancies. The annual age-adjusted incidence of urethral SCC is 4.3 per million in men and 1.5 per million in women. Due to the rarity of the disease, there are a limited number of prospective randomized controlled trials to evaluate the optimal management of locally advanced urethral SCC. Here, we present the case of a 47-year-old man with stage IIIB urethral squamous cell cancer that showed complete clinical and pathologic response to neoadjuvant chemoradiation with only 5-flurouracil after incomplete response to traditional chemotherapy with paclitaxel, ifosfamide, and cisplatin (TIP).